Consumption of red meat and whole-grain bread in relation to biomarkers of obesity, inflammation, glucose metabolism and oxidative stress - Montonen, Jukka; Boeing, Heiner; Fritsche, Andreas; Schleicher, Erwin; Joost, Hans-Georg; Schulze, Matthias B.; Steffen, Annika; Pischon, Tobias (European journal of nutrition, 2013)
Purpose To examine the association of red meat and whole-grain bread consumption with plasma levels of biomarkers related to glucose metabolism, oxidative stress, inflammation and obesity. Methods Our cross-sectional study was based on 2,198 men and women who were selected as a sub-cohort for an investigation of biological predictors of diabetes and cardiovascular diseases from the European Prospective Investigation into Cancer and Nutrition-Potsdam study. Circulating levels of glycated hemoglobin, adiponectin, hs-CRP, gamma-glutamyltransferase, alanine-aminotransferase, fetuin-A, HDL-cholesterol and triglycerides were measured from random blood samples. Diet and lifestyle data were assessed by questionnaires, and anthropometric data were measured. Results After multivariable adjustment, higher consumption of whole-grain bread was significantly ( P trend <0.05) associated with lower levels of GGT, ALT and hs-CRP, whereas higher consumption of red meat was significantly associated with higher levels of GGT and hs-CRP when adjusted for potential confounding factors related to lifestyle and diet. Further adjustment for body mass index and waist circumference attenuated the association between red meat and hs-CRP ( P = 0.19). Conclusions The results of this study suggest that high consumption of whole-grain bread is related to lower levels of GGT, ALT and hs-CRP, whereas high consumption of red meat is associated with higher circulating levels of GGT and hs-CRP.